2019
DOI: 10.3389/fimmu.2019.01345
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Evidence of T Cell Exhaustion and Senescence During Symptomatic Plasmodium falciparum Malaria

Abstract: T cells play significant roles during Plasmodium falciparum infections. Their regulation of the immune response in symptomatic children with malaria has been deemed necessary to prevent immune associated pathology. In this study, we phenotypically characterized the expression of T cell inhibitory(PD-1, CTLA-4) and senescent markers (CD28(-), CD57) from children with symptomatic malaria, asymptomatic malaria and healthy controls using flow cytometry. We observed increased expression of T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 55 publications
2
23
0
Order By: Relevance
“…Alternatively, abnormal cell death through apoptosis has also been indicated as another mechanism by which lymphocytes are depleted from blood during acute malaria infections [45]. This explanation is corroborated by the observation of high expression of exhaustion and senescence markers on T cells from children with symptomatic malaria compared to asymptomatic participants [46,47]. It is becoming increasingly clear that many chronic human infectious diseases, including P. falciparum infections [48,49] and HIV [50], are associated with the accumulation of atypical memory B cells that are characterized by the expression of exhausted markers, and a reduction of [51].…”
Section: Discussionmentioning
confidence: 91%
“…Alternatively, abnormal cell death through apoptosis has also been indicated as another mechanism by which lymphocytes are depleted from blood during acute malaria infections [45]. This explanation is corroborated by the observation of high expression of exhaustion and senescence markers on T cells from children with symptomatic malaria compared to asymptomatic participants [46,47]. It is becoming increasingly clear that many chronic human infectious diseases, including P. falciparum infections [48,49] and HIV [50], are associated with the accumulation of atypical memory B cells that are characterized by the expression of exhausted markers, and a reduction of [51].…”
Section: Discussionmentioning
confidence: 91%
“…It has been shown that RA patients had a multi-reactive anti-herpes IgM profile, which was associated with disease activity [46]. Also, expansions of CD28-T cells have also been documented in various chronic infections, including malaria [47], HIV [48] and human T-lymphotropic virus type-I (HTLV-1) [49]. More studies are necessary to explore the role of persistent infections during clinical progression in RA.…”
Section: Premature Immunosenescence In Ramentioning
confidence: 99%
“…This was supported by previous findings where apoptosis in lymph nodes and secondary lymphoid organs upon malaria infection was described. 133,134 In addition, it is also known that blood-stage malaria infections suppress dendritic cell (DC) responses by affecting DC maturation, [142][143][144] reducing surface expression of MHC-II 142,[145][146][147] and co-stimulatory molecule CD86, 146 inducing DC apoptosis 148,149 and impairing their ability to process and present parasite-derived antigens to T cells. 150,151 In line with this, reduced numbers of conventional DCs in the pLN of co-infected mice were also observed, suggesting that reduced expansion of CD4 + T cells might be due in part to the drop in DCs numbers associated with malaria.…”
Section: Immune Modulation Of Chikv T Cell Responses By Plasmodium mentioning
confidence: 99%
“…119 Taken together, these results suggest that the expansion, survival, and trafficking of pathogenic CHIKV-specific CD4 + T cells in the pLN/footpad axis are hampered by co-infections with Plasmodium parasites (Figure 1). Additionally, the contribution of T cell anergy 139,140 and exhaustion [141][142][143][144] extensively reported upon severe malaria infections remain to be explored.…”
Section: Impaired Expansion and Early Apoptosis Of Cd4 + T Cells In Dmentioning
confidence: 99%